Harmonisation and alignment: The double-edged swords of budget support and decentralised aid administration - Ole Winckler Andersen; Ole Therkildsen (Danish Institute for International Studies (DIIS), 2007)
The Paris declaration of 2005 on aid effectiveness is now part of the international consensus. It holds that increased use of budget support combined with decentralised aid administration will lead to transaction costs reductions (through better donor harmonisation of aid) and to enhanced local ownership (through better alignment of donor policies and practices with those of recipients). Both improvements are assumed to enhance aid effectiveness. This article argues that the partnership perspective, which underpins much of the official thinking about harmonisation and alignment, is not able to capture the divergent interests and strategies of the multitude of donors and recipients. A more realistic political economy perspective on the harmonisation and alignment agenda is therefore proposed. It assumes that: different actors do not have the same interests; staff incentives to work to improve harmonisation and alignment are often weak among both donor and recipient stakeholders; and information about stakeholder strategies, interests, budgets etc. is incomplete. It is demonstrated that analyses based on this alternative perspective could lead to markedly different conclusions from those contained in the generally accepted consensus. There is a strong need for further analyses to guide future policy decisions in this field using the political economy perspective.
Keywords: 330; Entwicklungshilfe; Entwicklungshilfekonditionen; Wirkungsanalyse; Entwicklungskooperation; Entwicklungsländer